Study of phase evolution and dielectric properties of Sr2Mn0.7Sn0.3O4 - Nirala, Gurudeo; Upadhyay, Shail (University of Novi Sad, Faculty of Technology, 2023)
Ruddlesden-Popper oxide Sr2Mn0.7Sn0.3O4 was synthesized by solid state method by calcining at different temperatures between 1200 and 1500 °C. The phase evolution during thermal treatments was investigated and it was shown that the powder calcined at 1500 °C and ceramics sintered at 1500 °C have single phase structure. Rietveld refinement of the XRD data confirmed tetragonal crystal structure having a = b = 3.9425 Å and c = 12.1230 Å lattice parameters and I4/mmm space group symmetry. Permittivity (ε), impedance (Z∗), dissipation factor (tan δ) and AC conductivity (σAC) of the samples were studied in the frequency range 1 kHz–2 MHz and temperature range 60–600 °C. An equivalent circuit comprising two parallel R-L elements and one constant phase element (CPE) model fitted the impedance data very well. Components of the equivalent circuit were correlated with compositional micro inhomogeneities in the sintered sample. Resonance-like feature observed in the dissipation factor at a particular temperature is attributed to the cancellation of capacitive and inductive reactants. Negative permittivity and loss of the sintered sample were compared with other ceramic oxides showing negative permittivity.
This paper published with affiliation IIT (BHU), Varanasi in Open Access Mode.
Keywords: dielectrics; negative permittivity; phase evolution; Ruddlesden-Popper oxides; solid state synthesis